2010
DOI: 10.30970/sbi.0403.109
|View full text |Cite
|
Sign up to set email alerts
|

Microflora activity of clued oil contaminated soil in rhizosphere of Carex hirta L. plants

Abstract: Досліджено вплив рослин Carex hirta на мікрофлору нафтозабрудненого ґрунту. Виявлено деякі групи мікроорганізмів за допомогою модифікованого методу обростання скелець. Встановлено позитивний вплив рослин Carex hirta на мікрофлору ґрунту, забрудненого нафтою (50 г/кг).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
1
2
0
2
Order By: Relevance
“…probably negligible (Fonseca-López et al, 2020). The lower levels of protease acti vity in planted contaminated soil is in line with L. Bunio (Bunio et al, 2010) who reported a decreased protease activity in the rhizosphere of plants Carex hirta L. This may be attributed to a competition between plants and bacteria for nutrients that resulted in a decrease in microbial activity. Significant variations in nitrogen species and phosphorus might be due to the joint effect of release and assimilation (Vavrek et al, 2005;Vinolas et al, 2001).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…probably negligible (Fonseca-López et al, 2020). The lower levels of protease acti vity in planted contaminated soil is in line with L. Bunio (Bunio et al, 2010) who reported a decreased protease activity in the rhizosphere of plants Carex hirta L. This may be attributed to a competition between plants and bacteria for nutrients that resulted in a decrease in microbial activity. Significant variations in nitrogen species and phosphorus might be due to the joint effect of release and assimilation (Vavrek et al, 2005;Vinolas et al, 2001).…”
Section: Resultssupporting
confidence: 76%
“…The urease activity in the oil-contaminated soil (at levels 0.35, 10.8, 20.5 and 50 g/kg of soil) was higher than that in the control (uncontaminated) and nutrient supplemented soils (John et al, 2016). The stimulating effect on soil urease activity was also determined for oil contamination conditions at the level of 50g/kg of soil and for contaminated soil planted with Carex hirta L. (Bunio et al, 2010). Legumes also have a stimulating effect on the activity of soil urease.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Наявність елементів живлення визначається діяльністю ґрунтової мікрофлори, а тому прямо залежить як від вологості, так і від аерованості ґрунту. В анаеробному гідрофобному нафтозабрудненому ґрунті різко зменшується кількість і знижується фізіологічна активність аеробних мікроорганізмів, задіяних у мінералізації органічних решток, найпомітніше -целюлозоруйнівних і нітрифікуючих бактерій [3,4,20,24]. Зокрема, кількість нітрифікуючих бактерій у нафтозабрудненому ґрунті може зменшуватися на 83 % [20].…”
Section: вступunclassified
“…Тож індукція активності ензимів ГС-ГОГАТ шляху та ймовірне нагромаджен ня глутамату в рослинах конюшини лучної за умов нафтозабрудненого ґрунту можуть бути спричинені потребою у збільшенні кількості проліну. Як з'ясувалося, вміст проліну в рослинах конюшини лучної на найпершій стадії росту в нафтозабрудненому ґрунті зростав усемеро в листках і втричі -у коренях рослин [10,36]. Тому його значення в адаптації рослин конюшини лучної до умов нафтозабрудненого ґрунту не викликає жодних сумнівів.…”
Section: схема асиміляції амонію гс-гогат шляхом (за [23])unclassified